Hubungan antara Perilaku Merokok dengan Timbulnya Kalkulus Gigi pada Mahasiswa Fakultas Kedokteran Di Surabaya - Fauzia Wulandari Ruslan; Wahyuni Dyah Parmasari (Universitas Wijaya Kusuma Surabaya, 2022)
This study generally aims to prove the emergence of dental calculus associated with smoking behavior in surabaya medical students. This smoking behavior includes smoking duration, number of cigarettes and smoking habits. Specifically for Analyzing smoking behavior in Medical students and analyzing dental health with indicators of the presence of dental calculus in Wijaya Kusuma University Surabaya students. This research is an experimental field research with an quantitative analytical approach to examine the symptoms of smoking behavior using design observational case control. The determination of sample, which means that the sample size for the case group is as large as the control group sample(1:1). In this study were 44 samples, namely 22 case group samples and 22 control group samples. From the results of data collection regarding smoking behavior were tested with non-parametric statistical inferential tests with the Spearman correlation test with significance value (r =0,05). The results of the study are of 100% of respondents who have mild smoking habits related to calculus in good condition as many as 10 people (45,5%). While the respondents had the habit of smoking related to calculus in moderate conditions as many as 12 people (54,5%) and there were no respondents in poor calculus conditions. The conclusion of the study showed that there was a relationship between smoking behavior and the incidence of dental calculus of active medical students at the medical faculty in Surabaya with a p-value of 0,025 less than 0,05. So it can be concluded that there is a relationship between smoking behavior and the formation of dental calculus.